Hermann-Broch-Handbuch - Kessler, Michael, 1944-; Lützeler, Paul Michael (Berlin ; Boston : De Gruyter, 2016)
"Considering his literary works-especially his novels-together with his writings on literature, philosophy, and politics, Hermann Broch is one of the most innovative German-language writers of the 20th century. This handbook was created in cooperation with an international research team. It presents Broch's life history along with all of his literary and essayistic output, analyzing and reassessing Broch's work in its multiple contexts."--
Includes bibliographical references and index.
Keywords: Broch, Hermann, -- 1886-1951 -- Criticism and interpretation; Broch, Hermann, -- 1886-1951.; Criticism, interpretation, etc